2006
DOI: 10.1051/0004-6361:20054620
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ks-excess stars in the 14 Myr open cluster NGC 4755

Abstract: Aims. We derive the structure, distribution of MS and PMS stars and dynamical state of the young open cluster NGC 4755. We explore the possibility that, at the cluster age, some MS and PMS stars still present infrared excesses related to dust envelopes and proto-planetary discs. Methods. J, H and K s 2MASS photometry is used to build CMD and colour-colour diagrams, radial density profiles, luminosity and mass functions. Field-star decontamination is applied to uncover the cluster's intrinsic CMD morphology and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 38 publications
5
66
0
Order By: Relevance
“…However, a small fraction appear to present an abnormal excess in (H − K s ), especially vdB 92, in the (J − H) × (H − K s ) diagram, which may come from PMS stars still bearing circumstellar discs, hence with excess in H (e.g. Furlan et al 2009;Bonatto et al 2006a). …”
Section: Fundamental Parametersmentioning
confidence: 99%
“…However, a small fraction appear to present an abnormal excess in (H − K s ), especially vdB 92, in the (J − H) × (H − K s ) diagram, which may come from PMS stars still bearing circumstellar discs, hence with excess in H (e.g. Furlan et al 2009;Bonatto et al 2006a). …”
Section: Fundamental Parametersmentioning
confidence: 99%
“…To uncover the intrinsic cluster CMD morphology, we use the field-star decontamination procedure described in Bonatto & Bica (2007b), previously applied in the analysis of low-contrast , embedded , young (Bonatto et al 2006c), faint ), old (Bonatto & Bica 2007a), or in dense-fields (Bonatto & Bica 2007b) OCs. The algorithm works on a statistical basis that takes the relative number densities of stars in a cluster region and offset field into account.…”
Section: Field-star Decontaminationmentioning
confidence: 99%
“…This tool was previously applied to the structural analysis of the OCs M 67 (Bonatto & Bica 2003), NGC 3680 (Bonatto et al 2004b), NGC 188 , NGC 6611 ), NGC 4755 (Bonatto et al 2006c), M 52 and NGC 3690 (Bonatto & Bica 2006) and the faint OCs BH 63, Lyngå 2, Lyngå 12 and King 20 ). The filters were defined based on the distribution of the decontaminated star sequences in the CMDs of open clusters.…”
Section: Structural Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Corti & Orellana (2013) give the distance to the cluster as 1.9±0.5 kpc and the age of ∼15 Myr. Bonatto et al (2006) estimated the cluster's age as 14 ± 2 Myr and concluded that the star formation in NGC 4755 began ≈14 Myr ago and proceeded for about the same length of time. Lyra et al (2006) find a value of 2040 ± 250 pc for the distance to the cluster and 7.1 ± 0.2 for the log age.…”
Section: Wind-blown Energy Deposit Of the Most Massive Stars Within Gmentioning
confidence: 99%